Comparative analyses of small molecule and antibody inhibition on glycoprotein‐mediated entry of Měnglà virus with other filoviruses. Issue 7 (5th April 2022) - Cooper, Laura; Galvan Achi, Jazmin; Rong, Lijun
Abstract: The ability of viruses in the Filoviridae family (Ebola virus [EBOV] and Marburg virus [MARV]) to cause severe human disease and their pandemic potential makes all emerging filoviral pathogens a concern to humanity. Měnglà virus (MLAV) belonging to the new genus Dianlovirus was recently discovered in the liver of bats from Měnglà County, Yunnan Province, China. The capacity of MLAV to utilize NPC1 as an endosomal receptor, to transduce mammalian cells, and suppress IFN response suggests that this potential pathogen could cause human illness. Despite great effort by researchers, only the viral genome has been recovered and isolation of live MLAV had been unsuccessful. Here using a pseudovirus model baring the MLAV glycoprotein (GP), we studied the protease dependence of the MLAV‐GP, and the ability of small molecules and antibodies to inhibit MLAV viral entry. Like EBOV and MARV, the MLAV‐GP requires proteolytic processing but like MARV it does not depend on cathepsin B activity for viral entry. Furthermore, previously discovered small‐molecule inhibitors and antibodies are MLAV inhibitors and show the possibility of developing these inhibitors as broad‐spectrum filovirus antivirals. Overall, the findings in the study confirmed that MLAV viral entry is biologically distinct but has similarities to MARV. Highlights: 1. In our study, we show that previously discovered small‐molecule filovirus inhibitors also inhibit Měnglà Virus (MLAV) entry. 2. Using a pseudovirus construct, we found that MLAV requires proteolytic processing for entry but is not dependent on cathepsin B. 3. This is the first study to show MLAV viral entry is biologically distinct but has similarities to Marburg Virus.